Estrutura, qualidade fisiológica e armazenamento de sementes de Caryocar brasiliense (Caryocaraceae) - Ângela Maria da Silva Sousa (2016)
Caryocar brasiliense Cambess., the pequizeiro, is a native tree fruitful importance of Brazilian Cerrado due to its use food and agro-industrial and medicinal potential. However, the species is threatened by deforestation, soil degradation and intense extraction of fruit. In addition, seed dormancy, which hinders the production of seedlings and planting on a commercial scale. It was verified the role of pyrene components in controlling germination, described the pattern of germination and early seedling development and evaluated the effect of gibberellic acid (GA3) and storage during seed germination. In addition, the results were related to environmental aspects associated with the adaptation of the species to places of occurrence. To describe the germination and initial development pattern of the seedlings were made two experiments, one with seeds isolated and one with seeds inserted in Cores. Each experiment was conducted with three pre-germination treatments (seeds with and without pre-soaking and treated with GA3) in eleven post-sowing time evaluation. The structures were described dry and germinated pyrenes and anatomical characteristics of seeds isolated and evaluated the length, width and depth of the seed and plumule and the water content over time, after sowing. To evaluate the effect of GA3 and storage on the seed germination, four experiments were conducted. In the first and second experiment, they used respectively isolated seeds and pyrenes stored for 2, 6, 13, 43 and 100 days. In the third experiment, pyrenes were used in freshly dispersed fruits soaked in five levels of GA3 (0, 125, 250, 375, 500 mg/L). In the fourth experiment, they used two storage times of pyrenes (0 and 20 days) and six doses of GA3 (0, 50, 100, 500, 1000, 2000 mg/L), and two additional treatments (without pre-imbibitions), one for each of the pyrenes storage time. They were evaluated the percentage of daily or weekly germination, germination speed index and at the end of the experiments, the percentage of non-germinated seeds and deteriorated. The structural components of the pyrene have direct influence on water absorption, dormancy and germination of C. brasiliense seeds. Isolated seeds of freshly dispersed fruits showed numbness and required exogenous application of GA3 to stimulate germination. The storage of pyrenes in a short period of time, 43 days, allowed to partially overcoming dormancy, however, increased by the deterioration and loss of seed vigor. The pyrene C. brasiliense has morphoanatomic and physiological adaptive mechanisms that control the germination and establishment of seedlings allocate in times favorable for survival.